Assessing quality of services by using servequal in Telecom Malaysia / Mohd Noor Mohd Tarmizi Koi - Mohd Tarmizi Koi, Mohd Noor (Faculty of Business and Management, 2016)
SERVEQUAL is one of the most important factors that a company need to take into consideration because it is important for a company to retain its customer and remain competitive in the business. Quality of service is the overall performance of service that company provides to its customer based. The purpose of this research is to identify the quality of services provided by Telekom Malaysia by using SERVEQUAL. Service quality is very importance in a sector that is becoming highly competitive. A survey of user for products and services in Telekom Malaysia was conducted to assess the quality of services provide by Telekom Malaysia. Service quality such as reliability, responsiveness, assurance, tangible, empathy. A total of 100 usable questionnaires were distribute and obtained. The finding show that the five independent variable reliability, responsiveness, assurance, tangible, empathy were important in determining and identifying the quality of services provide by Telekom Malaysia. Since the results of the research showed that quality of services is related to service quality such as reliability, responsiveness, assurance, tangible, empathy factors, therefore Telekom Malaysia need to consider these factors and provide the right services and other facilities that are essential in their quality and services.